Karakteristik kimia, susut masak, dan tingkat kesukaan daging analog berbasis jamur shitake dengan tepung tempe - Valentinus Priyo Bintoro; Ashghar Yusuf Randika Islamay Putra; Siti Susanti (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Tempeh is a local potential to make meat analog as an alternative to common materials such as isolated soy protein and gluten. This study aims to determine the effect of adding tempeh flour on chemical characteristics, cooking loss, and preference level of shitake mushrooms-based meat analog and to determine the optimal formulation. The experiment was conducted using a Completely Randomized Design with the addition of tempe flour 0%, 10%, 20%, and 30% with 5 replications. Analytical procedures include protein content, fat content, cooking loss, preference level, and statistical analysis. The results showed that the addition of tempeh flour significantly affected the chemical characteristics, cooking loss, and preference level of taste, texture, color, and overall shitake mushrooms-based meat analog. The highest protein content was 22,79%, obtained by 30%, the highest fat content was 3,08%, obtained by 30%, and the lowest cooking loss was 2,54%, obtained by 30%. The highest preference for taste attributes was